Intended and unintended effects: community perspectives on a performance-based financing programme in Malawi - Petross, Chisomo; McMahon-Rössle, Shannon A.; Lohmann, Julia; Chase, Rachel P.; Muula, Adamson S.; De Allegri, Manuela (BMJ global health, 2020)
Background  Several performance-b ased financing (PBF) evaluations have been undertaken in low-income countries, yet few have examined community perspectives of care amid PBF programme implementation. We assessed community members’ perspectives of Support for Service Delivery Integration - Performance-Based Incentives (‘SSDI-P BI’), a PBF intervention in Malawi, and explored some of the unintended effects that emerged amid implementation. - Methods  We conducted 30 focus group discussions: 17 with community leaders and 13 with mothers within catchment areas of SSDI-P BI implementing facilities. We analysed data using the framework approach. - Results  Community leaders and women had mixed impressions regarding the effect of SSDI-P BI on service delivery in facilities. They highlighted several improvements (including improved dialogue between staff and community, and cleaner, better-e quipped facilities with enhanced privacy), but also persisting challenges (including inadequate and overworked staff, overcrowded facilities and long distances to facilities) related to services in SSDI-P BI-implementing facilities. Further, respondents described how four targeted service indicators related to maternal risk factor management, antenatal care (ANC) in the first trimester, skilled birth attendance and couple’s HIV testing sparked unintended negative effects as experienced by women and communities. The unintended effects included women returning home for delivery, women feeling uncertain about their pregnancy status, women feeling betrayed or frustrated by the quality of care provided and partnerless women being denied ANC. - Conclusion  PBF programmes such as SSDI-P BI may improve some aspects of service delivery. However, to achieve system improvement, not only should necessary tools (such as medicines, equipment and human resources) be in place, but also programme priorities must be congruent with cultural expectations. Finally, facilities must be better supported to expect and then address increases in client load and heightened expectations in relation to services.